Mechanistic and kinetic studies on OH-initiated atmospheric oxidation degradation of benzo[α]pyrene in the presence of O2 and NOx. (January 2015) - Dang, Juan; Shi, Xiangli; Hu, Jingtian; Chen, Jianmin; Zhang, Qingzhu; Wang, Wenxing
Highlights: We studied a comprehensive mechanism of OH-initiated degradation of benzo[α]pyrene. Water plays an important role in the formation of nitro-benzo[α]pyrenes. The rate constants of crucial elementary steps were evaluated by the RRKM theory. Abstract: The degradation of polycyclic aromatic hydrocarbons (PAHs) in the atmosphere can lead to toxic derivatives which contribute to the carcinogenic potential of particulate organic matter. This paper aimed to investigate the mechanism of the OH-initiated oxidation degradation of benzo[α]pyrene (BaP), a cancer risk indicator. High-accuracy molecular orbital calculations were carried out, and all of the possible degradation pathways were discussed. The theoretical results were compared with the available experimental observation. The possible secondary reactions were also investigated. The rate constants of the crucial elementary steps were evaluated by using the Rice–Ramsperger–Kassel–Marcus (RRKM) theory. The dominant degradation products involve benzo[α]pyren-ol, nitro-benzo[α]pyrene, benzo[α]pyrene-7, 10-dione as well as several ring-opened products such as alkyl substituted benzanthraldehyde et al. In particular, water plays an important role in the degradation pathways leading to the formation of nitro-benzo[α]pyrene. This work provides a comprehensive investigation of the OH-initiated degradation of BaP and should help to clarify its potential risk.